Comparison of three 18F-labeled carboxylic acids with 18F-FDG of the differentiation tumor from inflammation in model mice. Issue 1 (December 2016) - Wang, Hongliang; Tang, Ganghua; Hu, Kongzhen; Huang, Tingting; Liang, Xiang; Wu, Zhifang; Li, Sijin
Abstract Background The aim of this study was to compare the properties and feasibility of the glucose analog, 2-18 F-fluoro-2-deoxy-D-glucose (18 F-FDG), three short18 F-labeled carboxylic acids, 18 F-fluoroacetate (18 F-FAC), 2-18 F-fluoropropionic acid (18 F-FPA) and 4-(18 F)fluorobenzoic acid (18 F-FBA), for differentiating tumors from inflammation. Methods Biodistributions of18 F-FAC, 18 F-FPA and18 F-FBA were determined on normal Kunming mice, and positron emission tomography (PET) imaging with these tracers were performed on the separate tumor-bearing mice model and inflammation mice model in comparison with18 F-FDG. Results Biodistribution results showed that18 F-FAC and18 F-FPA had similar biodistribution profiles and the slow radioactivity clearance from most tissues excluding the in vivo defluorination of18 F-FAC, and18 F-FBA demonstrated a lower uptake and fast clearance in most tissues. PET imaging with18 F-FDG, 18 F-FAC and18 F-FPA revealed the high uptake in both tumor and inflammatory lesions. The ratios of tumor-to-inflammation were 1.63 ± 0.28 for18 F-FDG, 1.20 ± 0.38 for18 F-FAC, and 1.41 ± 0.33 for18 F-FPA at 60 min postinjection, respectively. While clear tumor images with high contrast between tumor and inflammation lesion were observed in18 F-FBA/PET with the highest ratio of tumor-to-inflammation (1.98 ± 0.15). Conclusions Our data demonstrated18 F-FBA is a promising PET probe to distinguish tumor from inflammation. But the further modification of18 F-FBA structure is required to improve its pharmacokinetics.